2010
DOI: 10.5271/sjweh.3070
|View full text |Cite
|
Sign up to set email alerts
|

Transferring results of occupational safety and health cost-effectiveness studies from one country to another – a case study

Abstract: Verbeek J, Pulliainen M, Kankaanpää E, Taimela S. Transferring results of occupational safety and health costeffectiveness studies from one country to another -a case study. Scand J Work Environ Health. 2010;36(4):305-312.Objectives There are a limited number of studies about the cost-effectiveness of occupational health and safety (OSH) interventions. Applying the results of a cost-effectiveness study from one country to another is hampered by differences in the organization of healthcare and social security.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Verbeek et al66 demonstrated that economic evaluation results can be generalized from one country to another. Nevertheless, to enable the necessary calculations, researchers need to provide an extensive description of the intervention, a detailed list of resource use as well as information of the health care system in the original study and the allocation of costs to various stakeholders 66…”
Section: Discussionmentioning
confidence: 99%
“…Verbeek et al66 demonstrated that economic evaluation results can be generalized from one country to another. Nevertheless, to enable the necessary calculations, researchers need to provide an extensive description of the intervention, a detailed list of resource use as well as information of the health care system in the original study and the allocation of costs to various stakeholders 66…”
Section: Discussionmentioning
confidence: 99%
“…De hecho, en esta área hay pocos estudios que evalúen la costo-efectividad de las intervenciones en seguridad y salud en el trabajo, y los que existen tiene una baja calidad (66). Asimismo, también se observa que son pocos los trabajos de campo realizados que usen fuentes primarias de información.…”
Section: Discussionunclassified
“…The third stage of the translation research framework involves studies of evidence‐based technology and recommendations into well accepted OSH practice, through large‐scale delivery, dissemination, and diffusion research . The emphasis now is on external validity , resolving implementation challenges, and ensuring that an intervention or recommendation actually works within and can be integrated into a broad range of workplace settings.…”
Section: Four Stages Of Translation Research In Oshmentioning
confidence: 99%
“…Translation research is a multidisciplinary field of research composed of such disciplines as intervention effectiveness research, implementation research, health communication, and dissemination research, evaluation research, knowledge utilization, diffusion of innovations research, social marketing and commercial marketing, and surveillance and economic evaluation . However, application of these and related approaches in the OSH field has been limited and as Rantanen has noted, “such research on research is relatively scarce and even the paradigm for such studies is not well developed.”…”
Section: Introductionmentioning
confidence: 99%